Characterizing the N- and O-linked glycans of the PGF-CTERM sorting domain-containing S-layer protein of Methanoculleus marisnigri. (27th April 2022) - Kelly, John; Vinogradov, Evgeny; Robotham, Anna; Tessier, Luc; Logan, Susan M; Jarrell, Ken F
Abstract: The glycosylation of structural proteins is a widespread posttranslational modification in Archaea. Although only a handful of archaeal N-glycan structures have been determined to date, it is evident that the diversity of structures expressed is greater than in the other domains of life. Here, we report on our investigation of the N- and O-glycan modifications expressed by Methanoculleus marisnigri, a mesophilic methanogen from the Order Methanomicrobiales. Unusually, mass spectrometry (MS) analysis of purified archaella revealed no evidence for N- or O-glycosylation of the constituent archaellins, In contrast, the S-layer protein, identified as a PGF-CTERM sorting domain-containing protein encoded by MEMAR_RS02690, is both N- and O-glycosylated. Two N-glycans were identified by NMR and MS analysis: a trisaccharide α-GlcNAc-4-β-GlcNAc3NGaAN-4-β-Glc-Asn where the second residue is 2-N-acetyl, 3-N-glyceryl-glucosamide and a disaccharide β-GlcNAc3NAcAN-4-β-Glc-Asn, where the terminal residue is 2, 3 di-N-acetyl-glucosamide. The same trisaccharide was also found N-linked to a type IV pilin. The S-layer protein is also extensively modified in the threonine-rich region near the C-terminus with O-glycans composed exclusively of hexoses. While the S-layer protein has a predicted PGF-CTERM processing site, no evidence of a truncated and lipidated C-terminus, the expected product of processing by an archaeosortase, was found. Finally, NMR also identified a polysaccharide expressed by M. marisnigri and composed of a repeating tetrasaccharide unit of [−2-β-Rib f -3-α-Rha2OMe-3-α-Rha − 2-α-Rha-]. This is the first report of N- and O-glycosylation in an archaeon from the Order Methanomicrobiales.